SYNTHESIS OF PRASEODYMIUM GRAPHITIC-CARBON NITRIDE COMPOSITE (Pr/ g-C₃N₄) FOR THEIR BIOLOGICAL APPLICATIONS (Journal of Medical & Health Sciences Review, 2025)
The increasing prevalence of antibiotic resistance and oxidative stress-related disorders underscores the need for multifunctional materials with antimicrobial and antioxidant properties. This study focuses on synthesizing a Praseodymium-Carbon Nitride (Pr/ g-C₃N₄) composite and evaluating antimicrobial activity against “Escherichia coli” and “Staphylococcus aureus”. Antimicrobial efficacy was assessed using well-diffusion, disc-diffusion, and shake flask methods. The Pr/ g-C₃N₄ composite exhibited zones of inhibition of 9 mm and 8 mm in the well-diffusion and disc-diffusion assays, respectively, outperforming ciprofloxacin, which showed zones of 8.5 mm and 6 mm, respectively. Pr/ g-C₃N₄ achieved a 93% bacterial growth reduction in the shake flask method compared to ciprofloxacin’s 88%. Antioxidant activity evaluated using the DPPH assay revealed that Pr/ g-C₃N₄ demonstrated radical scavenging activity comparable to gallic acid. These findings highlight Pr/ g-C₃N₄ as a potent antimicrobial and antioxidant material, paving the way for its application in combating multidrug-resistant pathogens and oxidative stress-related diseases.Keywords: Praseodymium-Carbon Nitride (Pr/ g-C₃N₄) composite, Shake flask method, Well-diffusion Assay, Disc-diffusion assay, DPPH assay